Dissociation of motor control from motor awareness in awake sleepwalkers: An EEG study in virtual reality. (April 2022) - Rothacher, Yannick; Nguyen, Anh; Efthymiou, Evdokia; Werth, Esther; Baumann, Christian R.; Lenggenhager, Bigna; Brugger, Peter; Kunz, Andreas; Imbach, Lukas L.
Abstract: Recent behavioral evidence from a virtual reality (VR) study indicates that awake sleepwalkers show dissociation of motor control and motor awareness. This dissociation resembles the nocturnal disintegration of motor awareness and movement during episodes of sleepwalking. Here, we set out to examine the neural underpinnings of altered motor awareness in sleepwalkers by measuring EEG modulation during redirected walking in VR. To this end, we measured scalp EEG during ongoing motor behavior to provide information on motor processing and its modulation in VR. Using this approach, we discovered distinct EEG patterns associated to dual tasking and sub-threshold motor control in sleepwalkers compared to control subjects. These observations provide further electrophysiological evidence for the proposed brain-body dissociation in awake sleepwalkers. This study shows proof-of-principle that EEG biomarkers of movement in a VR setting add to the understanding of altered motor awareness in sleepwalkers. In a broader perspective, we confirm the feasibility of using the additional dimensionality in VR providing novel diagnostic biomarkers not accessible to conventional clinical investigations. In future studies, this approach could contribute to the diagnostic work-up of patients with a broad spectrum of neurological diseases.